Client Centered Counseling untuk meningkatkan harga diri pada penderita skizofrenia - Andi Dian Diarfah (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
Schizophrenia is a mental illness that can interfere with a person’s thoughts and behaviour. The subject of this case study is a 34-year-old man who has had schizophrenia since 1 year ago. The purpose of this intervention is to increase self-esteem in the subject. The assessment methods used were clinical interviews, observation, and psychological tests, namely WWQ, Graphic, Wartegg, and WAIS. The intervention provided was Client-Centered Counseling which was conducted for 7 sessions. The results of the intervention showed that the subjects began to assess themselves more positively.